Second-Year Biochar Residue and NPK Fertilizer Effects on Soil Mesofauna and Microbial Activity in Patchouli (Pogostemon cablin Benth.) - Any Kusumastuti; Made Same; Nurhasanah; AH. Maftuh Hafidh Zuhdi; Dian Latifathul Mar'ah (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2026)
Second-year biochar residue represents an understudied aspect of long-term soil amendment management, as its persistence in soil may influence biological communities differently over time. This study aimed to analyze the effects of second-year biochar residue and NPK fertilizer rates on soil mesofauna abundance and soil microbial activity in patchouli (Pogostemon cablin Benth.) cultivation. The experiment was arranged in a split-plot design with three replications. The main plot factor was second-year biochar residue rates (0, 10, and 20 ton ha-1), and the subplot factor was NPK fertilizer rates (0, 350, and 700 kg ha-1). Second-year biochar residue had no significant effect on soil mesofauna population, diversity index, dominance index, or microbial activity, while NPK fertilizer at 700 kg ha-1 significantly increased mesofauna population (24.33 individuals dm-³), diversity index (0.28), and dominance index (0.022). A total of 501 mesofauna individuals were identified, dominated by Acarina (67.3%) and Collembola (28.9%). Correlation analysis revealed strong positive relationships between mesofauna variables and soil physical factors, particularly temperature (r = 0.74) and moisture (r = 0.83), while soil chemical properties showed weak correlations. No significant interactions were observed between biochar residue and NPK fertilizer. These findings indicate that biochar’s stimulatory effects on soil biota diminish substantially after the first year. In contrast, NPK fertilization at 700 kg ha-1 effectively enhances soil mesofauna communities, which serve as indicators of soil biological health in patchouli cultivation systems.